Tenaga Kerja Indonesia di Malaysia (Studi Kasus TKW Asal Jawa Tengah dengan Pendekatan Fenomenologi) - Subadi, Tjipto (Universitas Muhammadiyah Surakarta, 2010)
This study aims to examine (1) the main cause of the female workers (FWs) in Malaysia from Central Java, Indonesia tortured by their employers, (2) the responsibility of the BP3TKI as an agency sending FWs if there is a problem of the FWs, (3) the steps the Indonesian and Malaysian government take to cope with the case of the Indonesian Labors (ILs) tortured by their employers, and (4) the model of cooperation for sending ILs to Malaysia professionally. The study used a phenomenology qualitative approach with a social paradigm definition of micro analysis. The subjects were the FWs in Malaysia tortured by their employers. The data gathering used an observation, documentation and interview method. The data analysis employed a method of first order understanding and second order understanding with an interactive model, including data reduction, data display and conclusion/verification. The findings show that (1) the main cause of torturing against the FWs is a miscommunication, low competency, cultural difference, feudalism behavior, bad institutional structure and difference in Act. (2) The responsibilities of the BP3TKI are legitimate and non-legitimate. (3) The steps the Indonesian government takes are (i) providing a guarantee to employers who do not have any problem for employing the Indonesian workers, (ii) establishing a Cooperation Agency for Problem Solving, (iii) giving one-day or one-week furlough to the FWs, (iv) if there is no furlough, an employer will give any compensation to them, (v) all the problems of the FWs must be resolved by the Indonesian and Malaysian Cooperation Association, and (vi) revising the Memo of Understanding (MoU) of the Labor Force. (4) The model of cooperation for sending the WFs to Malaysia is revising and completing the MoU, containing, among others, high wage, furlough, passport holders by (LIs), task force establishment, Labor Force Act, equal-working appointment, a great priority of human values and anti-slavery, discrimination, gender and anti-trade of human.